How to Distinguish Patients with pSS among Individuals with Dryness without Invasive Diagnostic Studies. (2nd May 2018) - Sebastian, Agata; Sebastian, Maciej; Misterska-Skóra, Maria; Woytala, Patryk; Jakuszko, Katarzyna; Wiland, Piotr
Abstract : In the course of pSS, inflammatory cell infiltration consists mainly of lymphocytes infiltrating exocrine glands, which leads to their impaired function. The characteristic feature is generalized dryness. The aim of this study was to attempt to answer the question whether it is possible to distinguish between patients with pSS and individuals with dryness caused by other pathologies without applying invasive studies. The study included 68 patients with pSS and 43 healthy controls with dryness. FS ≥ 1 was observed in 90% of patients with pSS (with or without dryness), and only in 23% of the control group (only with xerostomia). In the pSS group, anaemia (p = 0.0085 ), lymphocytopenia (p = 0.0006 ), elevated ERS (p = 0.001 ), higher RF titer, and ANA antibodies were noted. Configuration of anti-SSA + SSB + Ro52 antibodies was characteristic for the pSS group. Considering the clinical symptoms, statistically significant differences were noted between pSS patients and the control group in frequency (p = 0.02 ) and severity (p = 0.042 ) of fatigue, lymphadenopathy, major salivary gland involvement, and photosensitivity to UV light. In conclusion, invasive methods are pivotal in pSS diagnosis in this salivary gland biopsy. Chronic fatigue syndrome is more common in pSS patients and can be subjective distinguishing factor in the group of people with dryness.